A qualitative study about changes that parents experience through a pilot parenting support program to improve the quality of contact visits in non-kinship foster care - González-Pasarín, Lucía; Bernedo-Muñoz, Isabel María; García-Martín, Miguel Ángel (Elsevier, 2023)
Despite the important impact that contact with birth parents during non-kinship foster care can have on a child’s well-being, there are few psychoeducational programs aimed at improving the quality of visits. The purpose of this study was to analyze the perceptions of changes in birth parents who have completed the first program of this kind to be developed in Spain, here in its pilot application. The aim of the program Visits: a context for family development is to improve parents’ emotional, communication, and parenting competences, and it comprises a total of seven sessions: six individual sessions that take place in the hour prior to consecutive scheduled visits with the child, and one group session involving all participating birth parents. A total of five families began the program, and three mothers completed all seven sessions. We conducted semi-structured interviews with mothers before and after the intervention so as to explore their perceptions regarding changes in their parenting competences and the quality of visits with their child. These data were complemented by participant-observer notes taken by one of the researchers during program sessions. Through content and semantic network analysis of interviews, we were able to identify changes in relation to five aspects of contact visits following participation in the parenting program. The results suggest that the program has the potential to enhance the parenting competences of birth mothers, to improve parentchild interaction during contact visits, and to encourage collaboration between the birth and foster families. These preliminary findings support the utility of the program for improving the quality of contact visits between birth parents and their children in non-kinship foster care.
Keywords: Educación de niños - Crianza; Psychoeducational parenting program; Contact visit; Non-kinship foster care; Birth parents; Collaboration between families; Qualitative research